POTENSI DAN PERANAN PLTS SEBAGAI ENERGI ALTERNATIF MASA DEPAN DI INDONESIA - Boedoyo, Mohamad Sidik (Badan Pengkajian dan Penerapan Teknologi, 2012)
The success of national development will not be separated from the role of energy supply as a supporting facilitiy, as well as electricity. Given the potential of oil and gas energy are depleted, while coal which is abundant potential reserve but could bring a negative impact to the environment, the development of renewable energy resources for power generation is solution to achieve the national energy security. The utilization potential of solar power for electricity generation is a promising alternative, because a clean environment, unlimited resources and is available throughout the country. The tendency of diminishing the photovoltaic electricity generation cost as well as a variety of its applications to become a positive effect in the development of photovoltaic electricity generation. Integration of PLTS into the National Electrical system will require its own development strategy.